(untitled) (Research, Society and Development, 2020)
In the field of health, ozone therapy is a practice of global interest. Here, in Brazil, it is among the procedures present in the National Policy of Integrative and Complementary Practices in Health, of the Unified Health System, helped numerous treatments, due to the improvement of tissue oxygenation, immunomodulation, as well as its bactericidal, fungicidal and virustatic properties.In this context, the present study aimed to report the experience of an elderly patient, diagnosed with “Vulvar Craurosis”, complementing the traditional treatment with ozone therapy. It is, therefore, a study of qualitative methodology, defined as an experience report, that took place between the months of September and November 2019, in Niterói - Rio de Janeiro, Brazil. This patient was diagnosed with "Vulvar Craurosis" during a routine gynecological consultation, which is a chronic inflammatory disease of the skin and mucous membranes. The medical prescription consisted of topical corticosteroids and intravaginal estriol and, as a complementary treatment, ozone therapy was prescribed by the nurse. After a month, improvement of the lesion was observed, the prescription of corticosteroids was reduced and the frequency of estriol associated with ozone therapy sessions was maintained. The disease had an asymptomatic course, and treatment based on allopathy integrated with ozone therapy was maintained. The combination of conventional treatment with ozone therapy in “Vulvar Craurosis” was favorable in this study, however, further investigations are suggested, aiming to deepen the benefits of the use of ozone therapy associated with drugs normally indicated for the treatment of this pathology, seeking, finally, evidence more robust clinics.